Establishing an agenda for social studies research in marine renewable energy - Kerr, S.; Watts, L.; Colton, J.; Conway, F.; Hull, A.; Johnson, K.; Jude, Simon R.; Kannen, A.; MacDougall, S.; McLachlan, C.; Potts, T.; Vergunst, J. (Elsevier Science B.V., Amsterdam., 2014)
To date, academic research relating to Marine Renewable Energy (MRE) has largely focused on resource assessment, technical viability and environmental impact. Experiences from onshore renewable energy tell us that social acceptability is equally critical to project success. However, the speciﬁc nature of the marine environment, patterns of resource distribution and governance means experiences from onshore may not be directly applicable to MRE and the marine environment. This paper sets out an agenda for social studies research linked to MRE, identifying key topics for future research: (i) economic impacts; (ii) wealth distribution and community beneﬁts; (iii) communication and knowledge ﬂow; (iv) consultation processes; (v) dealing with uncertainty; (vi) public attitudes; and (vii) planning processes. This agenda is based on the ﬁndings of the ﬁrst workshop of ISSMER, an international research network of social scientists with interests in marine renewable energy. Importantly, this research agenda has been informed by the experiences of developers, regulators and community groups in Orkney. The Orkney archipelago, off the north coast of Scotland, is home to the most intense cluster of MRE research, development and deployment activity in the world today.